'Dopamine‐first' mechanism enables the rational engineering of the norcoclaurine synthase aldehyde activity profile. (9th February 2015) - Lichman, Benjamin R.; Gershater, Markus C.; Lamming, Eleanor D.; Pesnot, Thomas; Sula, Altin; Keep, Nicholas H.; Hailes, Helen C.; Ward, John M.
Abstract : Norcoclaurine synthase (NCS) (EC 4.2.1.78 ) catalyzes the Pictet–Spengler condensation of dopamine and an aldehyde, forming a substituted ( S )‐tetrahydroisoquinoline, a pharmaceutically important moiety. This unique activity has led to NCS being used for both in vitro biocatalysis and in vivo recombinant metabolism. Future engineering of NCS activity to enable the synthesis of diverse tetrahydroisoquinolines is dependent on an understanding of the NCS mechanism and kinetics. We assess two proposed mechanisms for NCS activity: (a) one based on the holo X‐ray crystal structure and (b) the 'dopamine‐first' mechanism based on computational docking. Thalictrum flavum NCS variant activities support the dopamine‐first mechanism. Suppression of the non‐enzymatic background reaction reveals novel kinetic parameters for NCS, showing it to act with low catalytic efficiency. This kinetic behaviour can account for the ineffectiveness of recombinant NCS in in vivo systems, and also suggests NCS may have an in planta role as a metabolic gatekeeper. The amino acid substitution L76A, situated in the proposed aldehyde binding site, results in the alteration of the enzyme's aldehyde activity profile. This both verifies the dopamine‐first mechanism and demonstrates the potential for the rational engineering of NCS activity. Abstract : Norcoclaurine synthase (NCS) catalyses the Pictet‐Spengler condensation of dopamine and an aldehyde. We assess the mechanism of NCS: computational and experimental data support a 'dopamine‐first' mechanism. Suppression of the background reaction reveals novel kinetic parameters for NCS, showing it acts with low catalytic efficiency. Finally, we verify the dopamine‐first mechanism by using it to engineer the enzyme's aldehyde activity profile.